(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2021)
This paper sets out from the perspective sociology of education and sociology of science, aiming: analyze the performance of students in nature sciences compared to other areas of knowledge in the National High School Exam; analyze the performance of candidates from public schools and private schools; present preliminary considerations that indicate how the presence of scientific laboratories in schools show some evidence of improvement in performance. The debate goes through by mobilizing the concept of scientific inequality and cultural goodwill to propose an interpretation of data that allows a comparison between the performance in natural sciences of students from several school systems by comparative analysis among public and private schools. The data selection it reports on the microdata of the National High School Exam (ENEM) — 2017 edition — which was investigated the results of students from the final year (senior year) who scores between 600 and 1000 points in natural sciences in order to compare these results with other areas of knowledge. The data show that students from public schools have proportionally more significant performance (between fields of knowledge) in hard sciences (and writing) than students from private schools. In addition, it is found in this range of score of the analysis a disproportion of representativeness of students from public schools on objection of private ones that can be interpreted as a marked characteristic of social and educational inequality in the country.